A review on extended role based access control (E-RBAC) model in pervasive computing environment - Bakar A.A.; Ismail R.; Jais J.; Manan J.-L.A. (2023)
Pervasive computing environments (PCE) derive the emergence of new pervasive application ranging from home to healthcare domain. These applications can be accessed from any place; at any time from anyone as in PCE users are mobile and may use mobile devices in accessing the resources and services. Thus controlling access to resource/services is a concern security question in PCE. Researchers have constructed many methods in order to restrict access in this environment such as Context Based Access Control (CBAC), Trust Based Access Control (TBAC) and recently many researchers have focused on enhance the Role Based Access Control (RBAC) model with other parameter/areas such as context information, business rule management, credential, neural network, trust and risk in order to come out with a new access control model that able to fit in PCE. This paper is to review the existing models that have extended RBAC model with those above mentioned areas. 2009 IEEE.